Application of The FR-04 Sensor for Automatic and Energy-Saving Clothesline Roof Control - Morina Buulolo; Carles Wiranto Laia; Nafaoli Buulolo; Roberto Kaban; Rimmar Siringo-ringo (Karya Techno Solusindo, 2025)
The application of the FR-04 sensor for automatic and energy-saving clothesline roof control is based on problems that people who have clothesline, so that dry clothes become wet with rainwater when the occupants of the house are outside the house. This system uses an FR-04 sensor to detect rain and an Arduino Uno microcontroller to control the Stepper Motor which opens and closes the clothesline roof. It is hoped that the creation of an automatic clothes drying roof design will help people reduce their anxiety when drying clothes in the rainy season. REFERENCESAlfiansyah, M. N., & Nugroho, A. (2023). Automatic clothesline control system using rain and light sensors for energy efficiency. International Journal of Electrical and Computer Engineering (IJECE), 13(1), 657–665. https://doi.org/10.11591/ijece.v13i1.pp657-665Arfianto, D. (2021). Prototipe jemuran otomatis dengan sensor hujan, LDR berbasiskan Arduino Uno R3 dan sistem monitoring menggunakan aplikasi Blynk. Seminar Nasional Manajemen, Informatika, dan Komputer(SENAMIKA), 269–277. https://ejurnal.teknokrat.ac.id/index.php/senamika/article/view/1230Fedianto, M. H. S., Aditiawan, F. P., & Al Haromainy, M. M. (2023). Pengujian sistem jaringan dokumentasi dan informasi menggunakan black box testing dan white box testing. Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 3(1), 213–221. https://doi.org/10.55606/jupsim.v3i1.2447Fitria, D., & Hidayat, A. (2022). Pengembangan sistem atap jemuran otomatis dengan sensor FR-04 dan konektivitas Blynk berbasis IoT. Jurnal Teknologi Rekayasa dan Inovasi, 4(3), 145–153. https://journal.inovasi.tech/index.php/jtri/article/view/895Hafidhin, M. I., Saputra, A., Rahmanto, Y., & Samsugi, S. (2020). Alat penjemuran ikan asin berbasis mikrokontroler Arduino UNO. Jurnal Teknik dan Sistem Komputer, 1(2), 59–66. https://doi.org/10.33365/jtikom.v1i2.210Jadhav, R. S., & Deshmukh, P. B. (2020). Design and development of an automated clothes drying system using IoT and environmental sensors. International Research Journal of Engineering and Technology (IRJET), 7(5), 3172–3178. https://www.irjet.net/archives/V7/i5/IRJET-V7I5661.pdfKencana, W., A. G. A. T. H. A., & Dan, F. T. I. (2020). Rancang bangun alat otomatis hand sanitizer dan ukur suhu tubuh mandiri untuk pencegahan Covid-19 berbasis IoT. Jurnal Transit, 1–6. https://ojs.trigunadharma.ac.id/index.php/transit/article/view/1226Kumar, A., & Gupta, R. (2020). IoT-enabled smart home energy-saving roof control system. International Journal of Innovative Technology and Exploring Engineering (IJITEE), 9(6), 120–125. https://doi.org/10.35940/ijitee.F3795.049620Li, X., Wang, S., & Zhao, Y. (2022). Smart IoT-based rain detection and automatic awning control system for household energy saving. Sensors, 22(14), 5318. https://doi.org/10.3390/s22145318Luo, H., Chen, W., & Li, P. (2021). Design of an automatic retractable roof system using IoT-based rain sensors and servo control. Measurement, 180, 109559. https://doi.org/10.1016/j.measurement.2021.109559Mustar, R. O. W. M. Y. (2017). Implementasi sistem monitoring deteksi hujan dan suhu berbasis sensor secara real time. Semesta Teknik, 20(1), 20–28. https://jurnal.umj.ac.id/index.php/semesta/article/view/1865Nguyen, T. P., & Le, H. N. (2021). Energy-efficient automatic roof control for smart homes using IoT sensors and adaptive algorithms. Journal of Building Engineering, 44, 103240. https://doi.org/10.1016/j.jobe.2021.103240Nurhasanah, L., & Ramadhan, M. (2023). Penerapan sensor FR-04 dan LDR pada sistem atap otomatis hemat energi menggunakan ESP32. Jurnal Riset Teknologi Elektro dan Komputer, 8(1), 33–42. https://ejurnal.teknokrat.ac.id/index.php/jrtek/article/view/2180Prasetyo, Y., & Zainuddin, A. (2020). Smart clothesline roof system based on FR-04 rain sensor and solar power controller. Jurnal Teknologi Informasi dan Elektronika, 5(4), 201–210. https://ejurnal.poliban.ac.id/index.php/jtie/article/view/1117Putra, A. P., & Wicaksono, D. (2022). Perancangan sistem jemuran otomatis berbasis Internet of Things menggunakan sensor FR-04 dan NodeMCU ESP8266. Jurnal Teknologi dan Sistem Terkini, 3(2), 101–110. https://doi.org/10.33365/jtst.v3i2.1142Rahman, M., & Anwar, S. (2023). IoT-based automatic roof control system using rainfall and humidity sensors for household energy saving. IEEE Access, 11, 45327–45338. https://doi.org/10.1109/ACCESS.2023.3267554Setiawan, F., & Haryanto, R. (2021). Sistem pengendali atap otomatis berbasis sensor hujan FR-04 dan sensor cahaya LDR dengan Arduino UNO. Jurnal Elektro dan Instrumentasi, 7(2), 88–95. https://jurnal.untidar.ac.id/index.php/jei/article/view/2230Sutanto, D., & Priyanto, A. (2022). Analisis kinerja sensor FR-04 dalam mendeteksi intensitas hujan pada sistem otomatisasi berbasis mikrokontroler. Jurnal Teknik Elektro Indonesia, 12(1), 55–63. https://doi.org/10.22146/jtei.v12i1.9803Taufik, M., & Rachman, A. (2021). Rancang bangun sistem atap jemuran otomatis menggunakan sensor hujan FR-04 berbasis Arduino Uno. Jurnal Teknik Elektro dan Komputer, 10(3), 112–119. https://doi.org/10.33369/jtekkom.v10i3.1789Zhang, Y., & Liu, C. (2024). IoT-based automatic rain detection system for smart domestic control applications. IEEE Internet of Things Journal, 11(2), 14012–14020. https://doi.org/10.1109/JIOT.2024.3360124